Implementation of the Educational Personnel Program for Elementary School Students in the Digital Age Using Google Classroom - Zuyyinasyam, Sophia; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Husaeni, Dwi Fitria Al (ASEAN Journal of Educational Research and Technology, 2023)
During the pandemic, online learning may be rampant, which is required by the government. Not a few students and teachers have difficulty using technology in this digital era, especially when collecting assignments. Therefore, we try to introduce the Google Classroom application with the aim of supporting online learning. With quantitative data collection methods, in the form of pre-test and post-test targeting elementary school students. The implementation of the training program is to provide videos in the form of material, so that students can observe, understand and practice it. Pretest results showed 95% and post-test 100%. From these results, students experienced an increase in learning. This is because students are given training before filling out the post-test. It can be concluded that, students agree about the existence of distance learning using Google Classroom. Because this application helps elementary students in collecting assignments.